Viability Analysis of the Development of STEM-Integrated Module on Alternative Energy Topics - Fitrianti, Alfia; Suwarma, Irma Rahma; Kaniawati, Ida (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
The study aims to determine the feasibility that STEM-based physics modules on alternative energy topics. The method used in this research is Research and Development with a 4D development model (Four-D Models). The validity test was conducted by two lecturers of the Master of Physics Education at the Indonesian University of Education and one physics teacher at a senior high school in Karawang. Readability test conducted by 7 students of grade x. The instruments used are material conformity instruments with STEM aspects, teaching material feasibility test instruments, and student readability sheets. Based on the results of the study, it can be concluded that the STEM-based physics module on the topic of alternative energy developed is feasible because it obtains valid criteria in each validation category, including the component of material suitability with STEM, 0.8 is categorized as Valid. In the feasibility component of teaching materials (modules), 0.79 is categorized as Valid. In the presentation component, 0.79 is categorized as Valid. In the linguistic component, 0.8 is categorized as Valid. Meanwhile, the readability test results conducted were at a high criterion of 86.43%. Thus, the development of STEM-based physics modules on alternative energy topics is "feasible" to be widely applied.